CO-WORKING SPACE DI BALANGAN - Sakrani Sakrani; Mohammad Ibnu Sa'ud (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
The shift in work patterns among modern society, particularly in the post-pandemic era, has increased the demand for flexible workspaces such as co-working spaces. Balangan, as a developing region in South Kalimantan, holds potential to be developed into a new center of productivity, especially for the younger generation and creative industry players. This research aims to design a co-working space in Balangan with an efficient space programming approach and the application of green building principles. The methods used include user needs analysis, site study, and the implementation of green architecture principles such as the use of natural lighting and ventilation, water management, and environmentally friendly materials. The result of this study is a co-working space design that offers comfort, energy efficiency, and integration with the local environment and culture.